Simple model for electron beam dynamics in laser modulators and radiation characteristics of steady-state microbunching storage ring - Cheng-Ying Tsai (蔡承颖); Xiujie Deng (邓秀杰) (Physical Review Accelerators and Beams)
Recent studies have actively explored the feasibility of a novel storage ring light source based on the steady-state microbunching (SSMB) mechanism. Many interesting investigations have been limited to single-particle or pure-optics effects. In SSMB storage rings, laser modulators, consisting of an undulator and a copropagating laser beam, are utilized to manipulate the longitudinal bunch length at the radiator position. When the electron bunch traverses the modulator undulator, it emits coherent undulator radiation around the resonant wavelength with respect to the modulation laser wavelength. To increase the intensity of the modulation laser, an enhancement cavity can be used. Within the enhancement cavity, the modulation laser field is confined in a closed path, allowing the intracavity power to be accumulated and enhanced. Within this cavity, not only is there an accumulated modulation laser from external injection, but also coherent undulator radiations—both of which influence the dynamics of the electron beam on subsequent turns. In this paper, we develop a simple model to analyze the electron beam dynamics in laser modulator cavities, including the effects of finite loss due to mirrors in the cavity and the externally injected laser power required to compensate for this energy dissipation, as well as the dynamical effects of coherent undulator radiation accumulated in the cavity over multiple turns. This model also allows the estimatation of the radiation characteristics in the radiator of the SSMB storage ring. Our method combines the beamline transfer matrices with a low-gain free-electron-laser oscillator model. The advantage of this approach lies in its ability to provide quick estimates for the aforementioned dynamical effects. We then discuss the feasibility of three recently proposed scenarios, namely, the amplifier SSMB, the frequency-beating SSMB, and the harmonic SSMB, in the presence of the aforementioned dynamical effects. The analysis indicates that all three scenarios remain feasible under the current preliminary design parameters.